Challenges to face in the use of videoconference and other technologies in our administration of justice (Acta Judicial Journal, 2023)
This work aims to offer a broad view of how videoconferencing and new technologies are essential tools in our Courts and Tribunals. However, we can say that they are still on the “to do list”. The shortcomings in videoconferencing systems that have traditionally been used have raised the possibility of using other systems or applications such as Zoom, Skype, Whatsapp, Google Meet, Teams. We will precisely try to analyze the main problems that are weighing down modern justice in our country and the challenges that we must face.
Keywords: videoconference; criminal process; tools; new technologies; technical means; challenges